设S,T是任意集合,如果S -T = Æ,则S = T。
A: 正确
B: 错误
A: 正确
B: 错误
B
举一反三
- 设S,T是任意集合,如果S -T = Æ,则S = T。
- 设S,T,M是集合,下列结论正确的是 未知类型:{'options': ['如果S∪T=S∪M,则T=M', '如果S-T=Φ,则S=T', '', ''], 'type': 102}
- 设集合s={0,1,2,3,4},T={2,3,5,6},则S∩T=______.
- 设S,T,M是集合,下列结论正确的是 A: 如果S∪T=S∪M,则T=M B: 如果S-T=Φ,则S=T C: [img=80x21]1802e98ee6ae7fc.png[/img] D: [img=143x25]1802e98eeeb756c.png[/img]
- 设S,T,M是集合,下列结论正确的是 A: 如果S∪T=S∪M,则T=M B: 如果S-T=Φ,则S=T C: [img=80x21]1803da661b9fd47.png[/img] D: [img=143x25]1803da6623a8bb7.png[/img]
内容
- 0
设全集U={1,2,3,4,5,6,7,8},集合S={1,3,5},T={3,6},则CU(S∪T)等于______.
- 1
设A,B,C和D均是集合,【图片】,则(R◦S)∩(R◦T)=R◦(S∩T)。()
- 2
设A,B,C和D均是集合,【图片】,则R◦(S∪T)=(R◦S)∪(R◦T)。()
- 3
设A,B,C和D均是集合,【图片】,则R◦(S∪T)=(R◦S)∪(R◦T)。()
- 4
设A,B,C和D均是集合,【图片】,则R◦(S∪T)=(R◦S)∪(R◦T)。()